Children Growth Analysis Reviewed From Nutrition Status Of Children Age 0-5 Years - Heri Saputro; Kristoforus Tnomel; Atik Setiawan Wahyuningsih; Joel Rey Ugsang Acob (PT. Griya Eka Sejahtera, 2023)
Background: Deviation of growth and development may occur if there are obstacles or interruptions in the process from intrauterine to adulthood. Deviations dap good at giving clinical manifestations of abnormalities in growth with or without developmental abnormalities. The purpose of the study to determine the effect of nutritional status on head growth in children 0-5 years.Methods: The design study is observational analytic with cross sectional approach. Respondents were taken using simple random sampling technique. Population in this research all toddlers in Kelurahan Tosaren Kediri as many as 327 children. Sample as many as 77 children under five. Independent variable is nutritional status, dependent variable of head growth. Results of statistical analysis using simple linear regression test.Results: The result of this research showed that almost all children under 5 years old in Tosaren Village with good nutrition status were 67 respondents (87.0%), almost all children under 5 years old in Tosaren Village with the appropriate head growth of 65 respondents (84, 4%) out of a total of 77 respondents. The results of data analysis showed that the level of significance p value = 0.000 thus H1 accepted which means there is influence between nutritional status and infant head growth tosaren 0-5 years in the village.Conclusion: Nutritional status with 0-5 year toddler growth head in tosaren sub-district, where the better the nutritional status of the toddler the better the growth of toddler head, this is because with good nutrition status of toddler eat body requirement of nutrition fulfilled, so growth of head of toddler good.